Circulating EBV DNA, Globulin and Nodal Size Predict Distant Metastasis after Intensity-Modulated Radiotherapy in Stage II Nasopharyngeal Carcinoma - Du, Xiao-Jing (J Cancer, 2016)
Background: The optimal treatment for early-stage nasopharyngeal carcinoma (NPC) remains controversial. Identification of prognostic factors for metastasis and tumor progression is urgently required to improve clinical decision-making for patients with American Joint Committee on Cancer (AJCC) 2009 stage II NPC from the endemic area. Methods: Consecutive newly-diagnosed patients (n=296) with non-disseminated, biopsy-proven stage II NPC were retrospectively reviewed; all patients received intensity-modulated radiotherapy and MRI follow-up. Plasma EBV DNA level, serum lactate dehydrogenase, serum albumin, serum globulin and leukocyte counts were measured before therapy. Survival rates were analyzed using the Kaplan-Meier method and log-rank test and multivariate Cox proportional hazards model. Results: Median follow-up was 50.2 months (range, 8-69.5 months). Multivariate analysis demonstrated a plasma Epstein-Barr virus (EBV) DNA level ≥ 4000 copies/mL, maximal axial diameter (MAD) of the cervical lymph nodes ≥ 30 mm and serum globulin level < 29.5 g/L were independent predictors of poor DMFS (P = 0.018; P = 0.019; P = 0.006, respectively). On the basis of these parameters, a prognostic model was developed as follows: 1) patients with no risk factors; 2) one risk factor; and 3) two or three risk factors. The 3-year distant metastasis-free survival rates for groups 1, 2 and 3 were 100%, 94.6% and 84.3%, respectively (P = 0.001). Conclusion: The prognostic model based on EBV DNA, serum globulin and nodal size may facilitate individualized treatment of patients with stage II NPC at high risk of distant metastasis.